2020
DOI: 10.3390/medicina56030101
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Clinical Outcome of DAA Containing Regimens in a Cohort of Patients in Calabria Region (Southern Italy)

Abstract: Background and objectives: In Italy, Hepatitis C Virus (HCV) infections are most prevalent in people older than 50 years of age, who often experience multi-morbidities, take co-medications, and have a long history of liver disease. These characteristics could potentially affect tolerability of HCV treatments and adherence in this subgroup. After achievement of sustained virological response (SVR), retention into care is very important both to detect the onset of possible complications and prevent further infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
2
11
2
Order By: Relevance
“…Although many studies have quantified the number of individuals with HCV who are lost from each step in the cascade of HCV care, few have explored the reasons for which these individuals become LTFU. The most commonly observed risk factor across studies has been age, with some suggesting that younger individuals are more likely to become LTFU 7,13–16 . In contrast, we did not find a significant association between age and LTFU in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although many studies have quantified the number of individuals with HCV who are lost from each step in the cascade of HCV care, few have explored the reasons for which these individuals become LTFU. The most commonly observed risk factor across studies has been age, with some suggesting that younger individuals are more likely to become LTFU 7,13–16 . In contrast, we did not find a significant association between age and LTFU in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…22 SVR, corresponding to HCV eradication, is obtained in more than 95% of the treated patients for most DAA-containing regimens in clinical trials, 23 which has also been confirmed in real-life studies including our cohort from which patients were selected for the present analysis based on availability of serum samples taken before and after DAA therapy. 24 However, some major clinical adverse events, such as arrhythmia, impairment of cardiac function, or increased prevalence of dyslipidemia have been reported. [25][26][27] In contrast, several studies have shown the clinical benefit of SVR induced by DAA treatment with respect to "hard" clinical endpoints such as CVD-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the control group was proportionally homogeneous with respect to gender, but not regarding age, which is because of the prevalence of the HCV infection in aged people in Italy. 24 Finally, the Note: P-values are from the interaction "covariate by time" calculated using repeated measures analysis of variance (ANOVA) to investigate the presence of different patterns from pretherapy baseline to SVR between the classes of the covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 97% of treated patients with DAAs achieved sustained virological response (SVR). According to our experience about a single-center cohort in Southern Italy, the SVR rate was 97% for the older age group, 96% for people under 65 years old, finally 94% and 100% for cirrhotic and non-cirrhotic patients, respectively [ 38 ].…”
Section: Discussionmentioning
confidence: 99%